2014
DOI: 10.5271/sjweh.3419
|View full text |Cite
|
Sign up to set email alerts
|

Workplace strength training prevents deterioration of work ability among workers with chronic pain and work disability: a randomized controlled trial

Abstract: The results show that strength training prevents deterioration of work ability among slaughterhouse workers with chronic pain and work disability. Thus, strength training should be highly prioritized when designing occupational health programs aiming at maintaining work participation among employees with musculoskeletal disorders exposed to highly repetitive and forceful job tasks.Affiliation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 31 publications
(47 reference statements)
5
83
0
1
Order By: Relevance
“…The present positive results on sickness absence days, pain and kinesiophobia following a single faceted intervention containing strength training, are in line with a previous study [39] where a preventive effect on work ability of a strength training programme was found. The programme was recommended on the short term to employees with musculoskeletal disorders exposed to repetitive and forceful job tasks.…”
Section: Ref N=27supporting
confidence: 80%
“…The present positive results on sickness absence days, pain and kinesiophobia following a single faceted intervention containing strength training, are in line with a previous study [39] where a preventive effect on work ability of a strength training programme was found. The programme was recommended on the short term to employees with musculoskeletal disorders exposed to repetitive and forceful job tasks.…”
Section: Ref N=27supporting
confidence: 80%
“…Even though many previous studies have reported no or only minor effects of interventions aiming to improve work ability, several recent studies shows that physical exercise at the workplace have the ability to influence work ability (48,49). For instance, ten weeks of strength training improved work ability in relation to physical and mental demands of the job -ie, the same questions as used in the present study -in both slaughterhouse workers with chronic pain and work disability and in healthcare workers (48,49).…”
Section: Sundsturp Et Almentioning
confidence: 52%
“…For instance, ten weeks of strength training improved work ability in relation to physical and mental demands of the job -ie, the same questions as used in the present study -in both slaughterhouse workers with chronic pain and work disability and in healthcare workers (48,49). Future research should investigate the effect of interventions aimed at increasing physical and mental capacity (eg, by physical activity and cognitive training), and reducing the physical and mental demands of the job (eg, by adjusting the work demands to the capacity of the workers), in workers with multiple chronic diseases and poor work ability.…”
Section: Sundsturp Et Almentioning
confidence: 78%
“…Interventions included vocational or multidisciplinary rehabilitation,38 39 43 ergonomic workplace assessments37 and exercise programmes 44–47. While the control groups in some studies received a passive comparator intervention such as provision of information,37–39 while in other studies the control group received an active comparator intervention such as individual physiotherapy43–45 therapy with work uptake advice46 and ergonomic training with education 47. A total of four outcomes were assessed: job loss, sick leave, pain and productivity.…”
Section: Resultsmentioning
confidence: 99%